Toxicological exposure to phthalates mixtures and human health risk assessment of drinking water and fruit drinks packaged in plastics and tetra pak cartons - Adegunwa, Abiodun Odunlami (2023)
Results of recovery analysis The results of the recovery analysis of the samples are presented in Table 1 and the chromatogram showing the relative abundance and retention of the detected phthalates in Fig. 1a–d. The reliability of the analytical procedures adopted in this study was tested on the basis of its sensitivity, recovery and accuracy. The obtained percentage recovery for the spiked phthalates ranged between 78.50 and 101.21% which fell within the acceptable range of 70–110% of recovery as stated by the assessment of European Union (2008). The recovery results established that the method adopted in this study is dependable and effective and so it is reproducible.